Women and the Civic Space in Namibia, South Africa and Zimbabwe: Constraints and Counter-constraints - Torque Mude; Peter Makaye; Tafadzwa Maramura; Gabriella Nguluwe (University of KwaZulu-Natal, 2023)
Civic space constitutes the substratum for women to be able to organise, communicate and participate in democratic processes, including claiming their rights, as well as influencing the trajectory of the political and socio- economic structures around them. With the proliferation of the recognition and participation of women in political processes, their attempts to occupy the civic space have also intensified. While the civic space is theoretically open for women’s civic participation, structural violence and cyber-violence have militated against women’s civic space visibility. This has culminated in the shrinking of the civic space for women’s articulation of political and socio-economic issues; especially in the African context. Against this backdrop, the objective of this paper is to examine the constraints women in Namibia, South Africa and Zimbabwe experience in operating in these spaces and the strategies they deploy to deal with these constrictions. Having said this, the paper intends to examine the manner in which physical, cyber and structural violence against Namibian, South African and Zimbabwean women manifests and affects their participation in civic spaces. Moreover, it Women and the Civic Space 245 explores the strategies deployed by women to counter the various forms of violence and other stumbling blocks inherent in the civic space. Data for this paper were generated from both primary and secondary sources and thematic analysis was used to analyse the data.